DEVELOPMENT OF SERVICES IN RELIGIOUS AND ECOLOGICAL AREAS. - Berdyorov Shokhbozjon , (TADQIQOTLAR.UZ, 2024)
Abstract: Quality is a crucial factor for staying competitive in the international tourism sector. Quality service is essential in tour operations to please, retain, and build loyalty among travelers. This research proposes a framework to examine how tourists' opinion of service quality affects satisfaction and loyalty. This research's t aims to address and explore the lack of existing services in religious and environmental facilities, exploring the need to add additional services and improve the quality of existing services. Research has been done to reveal its rich and unique tourism value. This study is based on quantitative research and oral interviews. Today, ecological and religious pilgrimage tourism is developing on a large scale, therefore, this research serves to further expand this field, because this object effectively contributes to the economy and improves the standard of living of the local population.